Peranan Kejaksaan Menangani Perkara Tindak Pidana Bidang Perlindungan dan Pengelolaan Lingkungan Hidup: The Role of the Prosecutor's Office in Handling Criminal Cases in the Field of Environmental Protection and Management - Bahar Elfudllatsani; Lubis, Muhammad Ikhsan (The Prosecutor Law Review, 2025)
The development of attention and awareness of the world community is influenced by the development of science related to the impacts and serious threats that arise for human health and the environment. The new paradigm is that environmental destruction is considered a form of human rights violation. Human rights are not only about protecting "humans", but also protecting the environment as an integral part of fulfilling human rights. In ensuring the fulfillment of human rights related to the environment, it is getting stronger after the precautionary principle is concretized with the enactment of Law Number 32 of 2009. The statutory and conceptual approach method relates to the role of the prosecutor's office in handling environmental protection and management cases, the right to a good and healthy environment and court decisions. Normatively, guidelines for public prosecutors and prosecutors in handling cases in the field of environmental protection and management in UUPPLH are accommodated. In general, the authority is divided into preventive and repressive aspects. Institutionally, the Attorney General's Office is part of the executive domain, so that its authority to act in the fields of civil and state administration is the implementation of government policy.